Improving the model of payment for medical care for chronic viral hepatitis C in the framework of the implementation of the Program of State Guarantees of Free Provision of Medical Care to Citizens for 2023 and for the planned period of 2024-2025 - V. V. Omelyanovskiy; I. A. Zheleznyakova; A. V. Zuev; O. S. Plakhotnik; O. A. Volkova; L. M. Davydova; G. V. Trifonova; E. V. Semakova; E. A. Prokhorovich; A. S. Volkova (IRBIS LLC, 2023)
Background. In 2021, new clinical guidelines for the treatment of chronic hepatitis C virus (HCV) in adults were published that did not contain interferon drug therapy regimens. Current therapy of chronic HCV is based on modern drugs of direct-acting antivirals (DAA). In this regard, the model of diagnosis-related groups (DRG) with the use of interferon-containing drugs as etiotropic therapy, which has been in effect until now, has lost its relevance and cannot be used to pay for cases of medical care for chronic HCV within the framework of the Program of State Guarantees of Free Medical Care to Citizens for 2023 and for the planning period of 2024-2025 (PSG). Objective: to improve the DRG model to pay for medical care for chronic HCV in a day hospital based on current clinical recommendations.Material and methods. Regulatory legal documents on the subject of the study, proposals and expert opinions of specialists, as well as feedback from public organizations, including patients, regarding the payment of medical care for chronic HCV, sent as part of a public discussion of the draft PSG, were studied. For the calculations were used: the current version of the clinical recommendations "Chronic viral hepatitis C"; impersonal personalized information of the database of registers of bills for payment for medical care for 2020-2021; the state register of manufacturers' maximum selling prices for medicines included in the list of vital and essential drugs.Results. A DRG model was developed to pay for medical care during drug therapy of chronic HCV, including for children. When calculating the model, the cost of medicines, patient days and the principles of accounting for the duration of hospitalization were updated.Conclusion. The developed DRG model to pay for medical care for chronic HCV in a day hospital with the use of drug therapy regimens with DAA recommended by clinical guidelines, including for children with HCV, contributes to improving the effectiveness of the system of payment for medical care provided as part of the implementation of the PSG and accessibility of medical care for this contingent of patients.